Animasi Digital Berbasis Tokoh Kearifan Lokal Sebagai Metode Peningkatan Kemandirian Anak dengan Cerebral Palsy - Prawesti, Indah; Sari, Ignasia Yunita; Febrianti, Santahana (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2021)
Cerebral Palsy (CP) is a motor disability, which is accompanied by characteristics of cognitive impairment, communication deficits, muscle rigidity, dysphagia and other sensory system problems. The prevalence of CP worldwide was 2,11 per 1000 live births, while in Indonesia based on 2010 data the incidence was 0,9 per 1000 live births. Difficulties often experienced by children with CP are routine activities including bathing, eating, wearing and taking off clothes and other physical activities. The aims of education for children with CP is to increase children’s independence in functional performance so that they are able to carry out daily activities. The purpose of this study was to determine the effect of education using digital animation on the independence of children with CP in self-care grooming. This research is aquasi-experimental study with pre test post test design without control, sampling method is a total population of 13 CP childrens and analysis using wilcoxon test. The result showed that the self-care grooming independence average before the intervention was 32,38±13,06 and after the intervention was 33,07±12,13 so that the mean difference was 0,69. The wilcoxon test result obtain p value 0,351, so there is no significant difference in the value of children’s independence in doing self-care grooming through digital animation education.